2021
DOI: 10.1002/soej.12538
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of state COVID‐19 reopening policy on human mobility and mixing behavior

Abstract: This study quantifies the effect of the 2020 state COVID economic activity reopening policies on daily mobility and mixing behavior, adding to the economic literature on individual responses to public health policy that addresses public contagion risks. We harness cellular device signal data and the timing of reopening plans to provide an assessment of the extent to which human mobility and physical proximity in the United States respond to the reversal of state closure policies. We observe substantial increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Our event study analyses showed that physicians responded quickly to decreased demand by becoming less selective about patient insurance in April 2020. As states reopened and some interactions resumed in subsequent months (Nguyen et al, 2021), reversion to greater selectivity was equally quick. The primary care system also enacted a rapid and substantial shift from in‐person to telemedicine visits during the first 2 months following stay‐at‐home orders.…”
Section: Discussionmentioning
confidence: 99%
“…Our event study analyses showed that physicians responded quickly to decreased demand by becoming less selective about patient insurance in April 2020. As states reopened and some interactions resumed in subsequent months (Nguyen et al, 2021), reversion to greater selectivity was equally quick. The primary care system also enacted a rapid and substantial shift from in‐person to telemedicine visits during the first 2 months following stay‐at‐home orders.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that SAHs and emergency announcements effectively limited mobility, restricting individuals' ability to move freely during lockdown periods (Alexander & Karger, 2023;Dave et al, 2021;Fang et al, 2020;Gupta et al, 2020). Prior studies also show that the post-lockdown rebound in mobility was relatively small compared to initial mobility reductions (Nguyen et al, 2021), potentially because people voluntarily practiced social distancing to avoid infection, besides complying with legal lockdown orders (Goolsbee & Syverson, 2021). Consumers reduced spending on things like eating out but increased spending on food delivery (Alexander & Karger, 2023), while also purchasing more shelf-stable, ultraprocessed, and energy-dense foods and alcohol (Bhutani & Cooper, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we contribute to the rapidly growing literature using aggregate GPS data to study the effect of policies trying to contain the spread of COVID‐19 on mobility patterns (Allcott et al, 2020; Dasgupta et al, 2020; Dave et al, 2020; Schlosser et al, 2020; Nguyen et al, 2021; Wellenius et al, 2021; Breidenbach and Mitze, 2022). The use of GPS data is one of the main alternatives to using surveys (Jørgensen et al, 2021; Briscese et al, 2023), which likely do not provide reliable data on mobility due to social desirability bias (Daoust et al, 2020).…”
Section: Introductionmentioning
confidence: 99%